Outbreak of SARS-CoV2: Pathogenesis of infection and cardiovascular involvement - Hamideh Amirfakhryan; Fatemeh safari (Hellenic Journal of Cardiology, 2021)
Since the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) has emerged from China, the infection (novel corona virus disease-2019, COVID-19) has affected many countries and led to many deaths worldwide. Like SARS-CoV, angiotencin converting enzyme (ACE)2 as a functional receptor for SARS-CoV2 is essential for the virus to make an entry into the cell. ACE2 is a part of Renin-Angiotensin-Aldosterone System, which is expressed in several organs that opposes the angiotensin (Ang) II functions by converting Ang II to Ang (1-7), the one with vasodilation effects. The death rate of COVID-19 is estimated to be approximately 3.4%; however, some comorbid conditions like underlying cardiovascular disease, hypertension, and diabetes increase the risk of mortality. In addition, cardiovascular involvement as a complication of SARS-CoV2 could be direct through either ACE2 receptors that are expressed tremendously in the heart, or by the surge of different cytokines or by acute respiratory distress syndrome-induced hypoxia. Traditional risk factors could aggravate the process of COVID-19 infection that urges the triage of these high-risk patients for SARS-CoV2. Currently, there is no effective, proven treatment or vaccination for COVID-19, but many investigators are struggling to find a treatment strategy as soon as possible. Some potential medications like chloroquine by itself or in combination with azithromycin and some protease inhibitors used for the treatment of COVID-19 have cardiovascular adverse effects, which should be kept in mind while the patients taking these medications are being closely monitored.